Mental Health Problems Among Secondary School Teachers’ in Nepal - Bhagwan Aryal; Sujala Mathema; Tanka Maya Pokharel; Sharmila Pokharel; Mohan Kumar Sharma (SAGE Open)
School teachers often face stress, tension, frustration, and nervous breakdowns, which can lead to major mental illnesses. Financial difficulties, inactivity, and school-related challenges can all contribute to such issues. The objective of this study is to explore the mental health problems among secondary-level teachers’ in Nepal. This study utilized a multi-stage cross-sectional survey design, employing both purposive and proportionate sampling procedures representing three regions Rasuwa (Mountain), Bhaktapur (Hill), and Chitwan (Terai) of Nepal. A total of 344 secondary-level teachers filled out survey questionnaire. Two sorts of analysis, univariate and bivariate were employed using SPSS 25 version. The study revealed that school type is significantly associated to feeling of stress, p  < .05. Just a single variable of age group among secondary-level teachers demonstrated a significant association with the occurrence of nervous breakdowns, p  < .001. In contrast, none variables are associated to feeling any harsh tension, frustration, depression, and unhappiness at work. Female teachers, those aged 35 to 39, and institutional school teachers reported higher level of stress each day. Majority of teachers experienced some form of harsh mental tension, frustration, and unhappiness at work. Female teachers and younger age groups such as ≤24 and 30 to 34 years reported higher mental suffering. Prolonged mental distress among educators can deteriorate in teaching quality and their roles as effective models. This pointed the necessity for targeted interventions, including counseling and stress management, particularly for high-risk groups like female teachers, aged 35 to 39, and institutional educators to enhance well-being and job performance.